Adrenal insufficiency causes life-threatening arrhythmia with prolongation of QT interval - Komuro, Jin (Heart Vessels, 2015)
A 63-year-old woman who had hypopituitarism was re-admitted to our hospital because of fever, diarrhea and disturbance of consciousness with life-threatening arrhythmia due to prolongation of the QT interval. She has been treated with hydrocortisone consequently, and has shown few ventricular arrhythmias with normalization of the QT interval. There have been several reports showing the case of prolonged QT interval with adrenal insufficiency, but there are few reports of isolated adrenocorticotropic hormone deficiency without any electrolytes imbalance that showed polymorphic ventricular tachycardia associated with QT prolongation. We discuss some possible mechanisms of how adrenal insufficiency causes life-threatening arrhythmia. Since lack of glucocorticoid hormone might induce prolongation of the QT interval, patients with adrenal insufficiency should be paid attention as candidates of lethal arrhythmias particularly when exposed to excessive stresses.